Epigenome-wide effects of vitamin D on asthma bronchial epithelial cells. Issue 9 (2nd September 2019) - Boutaoui, Nadia; Puranik, Sandeep; Zhang, Rong; Wang, Ting; Hui, Daniel H.; Brehm, John; Forno, Erick; Chen, Wei; Celedón, Juan C.
ABSTRACT: Vitamin D is a nutrient and a hormone with multiple effects on immune regulation and respiratory viral infections, which can worsen asthma and lead to severe asthma exacerbations. We set up a complete experimental and analytical pipeline for ATAC-Seq and RNA-Seq to study genome-wide epigenetic changes in human bronchial epithelial cells of asthmatic subjects, following treatment of these cells with calcitriol (vitamin D3) and Poly (I:C)(a viral analogue). This approach led to the identification of biologically plausible candidate genes for viral infections and asthma, such as DUSP10 and SLC44A1.